Give it a rest: a systematic review with Bayesian meta-analysis on the effect of inter-set rest interval duration on muscle hypertrophy - Singer, Alec; Wolf, Milo; Generoso, Leonardo; Arias, Elizabeth; Delcastillo, Kenneth; Echevarria, Edwin; Martinez, Amaris; Androulakis Korakakis, Patroklos; Refalo, Martin C.; Swinton, Paul A.; Schoenfeld, Brad J. (Frontiers in Sports and Active Living, 2024)
We systematically searched the literature for studies with a randomized design that compared different inter-set rest interval durations for estimates of pre-/post-study changes in lean/muscle mass in healthy adults while controlling all other training variables. Bayesian meta-analyses on non-controlled effect sizes using hierarchical models of all 19 measurements (thigh: 10; arm: 6; whole body: 3) from 9 studies meeting inclusion criteria analyses showed substantial overlap of standardized mean differences across the different inter-set rest periods (binary: short: 0.48 [95%CrI: 0.19 to 0.81], longer: 0.56 [95%CrI: 0.24 to 0.86]; Four categories: short: 0.47 [95%CrI: 0.19 to 0.80], intermediate: 0.65 [95%CrI: 0.18 to 1.1], long: 0.55 [95%CrI: 0.15 to 0.90], very long: 0.50 [95%CrI: 0.14 to 0.89]), with substantial heterogeneity in results.Univariate and multivariate pairwise meta-analyses of controlled binary (short vs longer) effect sizes showed similar results for the arm and thigh with central estimates tending to favor longer rest periods (arm: 0.13 [95%CrI: -0.27 to 0.51]; thigh: 0.17 [95%CrI: -0.13 to 0.43]). In contrast, central estimates closer to zero but marginally favoring shorter rest periods were estimated for the whole body (whole body: -0.08 [95%CrI: -0.45 to 0.29]). Subanalysis of set end-point data indicated that training to failure or stopping short of failure did not meaningfully influence the interaction between rest interval duration and muscle hypertrophy. In conclusion, results suggest a small hypertrophic benefit to employing inter-set rest interval durations >60 seconds, perhaps mediated by reductions in volume load. However, our analysis did not detect appreciable differences in hypertrophy when resting >90 seconds between sets, consistent with evidence that detrimental effects on volume load tend to plateau beyond this time-frame. KEYWORDS: rest period; recovery interval; muscle growth; muscle development; muscle thickness; muscle cross-sectional area * In cases where studies equated sets between conditions, fewer repetitions may have been performed in the shorter rest conditions over multiple sets of a given exercise.